1999
DOI: 10.1159/000016518
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Remineralization of in vivo and in vitro Formed Enamel Lesions

Abstract: Thin sections of natural white spot enamel lesions (WS) and of artificial in vitro lesions (VL) were remineralized simultaneously in vitro. The sections, clamped in a PMMA holder, were microradiographed at baseline and after remineralization in a calcium– and phosphate–containing solution (pH = 7.0; 1 ppm F) after 2 and 4 weeks. All data were analyzed with respect to baseline. The results show that the lesion depth values did not change significantly during 2 and 4 weeks of remineralization. The mineral accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 12 publications
8
48
0
1
Order By: Relevance
“…** Side effects when taken in excess are abdominal discomfort, flatulence, softened stools, and diarrhea. • In vitro models 22,23 • Animal models [24][25][26][27][28] • In vivo monitoring of acid production by human dental plaque bacteria using indwelling pH sensor (human plaque pH method) 10,11,[29][30][31] • Intraoral cariogenicity tests or demineralisation/remineralisation models 32,33 . At present, all four of the above examinations are required to evaluate the cariogenicity of an individual sugar substitute.…”
Section: Methods Of Evaluating the Cariogenicity Of Sugar Substitutesmentioning
confidence: 99%
See 1 more Smart Citation
“…** Side effects when taken in excess are abdominal discomfort, flatulence, softened stools, and diarrhea. • In vitro models 22,23 • Animal models [24][25][26][27][28] • In vivo monitoring of acid production by human dental plaque bacteria using indwelling pH sensor (human plaque pH method) 10,11,[29][30][31] • Intraoral cariogenicity tests or demineralisation/remineralisation models 32,33 . At present, all four of the above examinations are required to evaluate the cariogenicity of an individual sugar substitute.…”
Section: Methods Of Evaluating the Cariogenicity Of Sugar Substitutesmentioning
confidence: 99%
“…However, these effects are not unique to xylitol [32][33][34]42,54 . In fact, the inhibitory effect of xylitol on the growth of mutans streptococci is rather weak, and the remineralisation activity is common to all sugar alcohols.…”
Section: How Do Sucrose Substitutes Help To Prevent Dental Caries?mentioning
confidence: 99%
“…Even under circumstances favorable for remineralization in vivo, early carious lesions may fail to achieve remineralization. The proteins in human saliva, such as statherin, a tyrosine-rich acidic peptide, acidic proline-rich phosphoproteins (PRPs), or albumin, may hinder remineralization by infiltrating into the lesions [4][5][6] . The involvement of such proteins, however, remains unclear because of the lack of any appropriate assay system.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a great number of in situ and in vitro investigations were conducted in the following decades and showed that remineralisation occurs in newly formed artificial enamel lesions (Mellberg et al, 1986, Dijkman et al, 1990, Manning and Edgar, 1992, as well as in lesions formed under plaque in situ (Dijkman et al, 1986) and in vivo (Øgaard et al, 1988). With regard to the baseline mineral loss, it has been shown that the remineralisation of newly formed white spot lesions and in vitro formed lesions take place in the same way (Iijima et al, 1999).…”
Section: Enamel Remineralisation Therapiesmentioning
confidence: 99%